A Circulating MicroRNA Signature Capable of Assessing the Risk of Hepatocellular Carcinoma in Cirrhotic Patients - Ya-Hui Huang (Nature Portfolio, 2017)
Abstract With the availability of potent antiviral therapies, complete suppression of hepatitis B virus (HBV) replication and total eradication of hepatitis C virus (HCV) can now be achieved. Despite these advances, hepatocellular carcinoma (HCC) still develops in a substantial proportion of cirrhotic patients, suggesting that host factors remain critical. Dysregulation of miRNAs is noted in many cancers, and circulating miRNAs can be readily assayed. In this study, we aimed to develop a circulating miRNA signature to assess the risk of HCC in cirrhotic patients. We first discovered that HBV- and HCV-related cirrhotic patients had distinguishable circulating miRNA profiles. A cohort of 330 cirrhotic patients was then compared against a cohort of 42 early HCC patients with complete remission. A score comprising 5 miRNAs and a binary etiology variable was established that was capable of differentiating between these two groups (AUC = 72.5%, P < 0.001). The 330 cirrhotic patients were further stratified into high- and low-risk groups, and all patients were longitudinally followed for 752 (11–891) days. Of them, 19 patients developed HCC. The high-risk group had significantly higher cumulative HCC incidence (P = 0.038). In summary, a circulating miRNA-based score was developed that is capable of assessing HCC risks in cirrhotic patients.